THE DYNAMICS OF COLORS, CONSUMER PERCEPTIONS, AND PURCHASING INTENTIONS OF THE PRIMAVERAVESPA PRODUCTS: A REVIEW OF YOUNG CONSUMER BEHAVIOR - Nugroho, Dian Ari; Hendrawan, Dimas (Universitas Brawijaya, Indonesia, 2017)
This study aims to dete mine if the Primavera Vespa product color differences have significant influence on the Vespa product consumer perceptions and also to determine if the Primavera Vespa consumer perceptions on the products have a significant influence on the purchasing intention of Primavera Vespa product itself. This experimental research using 24 young consumers as respondents with purposive sampling as sampling technique. Data is collected through questionnaires with Likert scale. Hypothesis testing using different ANOVA test and Simple Regression Analysis. The results of this study indicate if the color difference of Primavera Vespa product has a significant influence on the consumer perception. The study also found if the color perceptions of Primavera Vespa products such as azzuro marechiaro, blue midnight, montebianco, nero volcano, and rosso dragon types have a significant effect on purchasing intentions to the product.